Forced convective heat transfer of tubes sintered with partially-filled gradient metal foams (GMFs) considering local thermal non-equilibrium effect. (5th June 2018) - Xu, Z.G.; Qin, J.; Zhou, X.; Xu, H.J.
Highlights: Gradient metal foams' forced convective heat transfer is numerically studied. Morphology gradients deeply influence solid and fluid temperature profile. The velocity decreases with increasing interfacial radius. Porosity gradient effect on friction factor increases with increasing pore-density. Abstract: Gradient metal foams (GMFs) are novel porous structures and have great potential in heat transfer performance. In the present study, fully developed forced convective heat transfer in tubes sintered with partially-filled GMFs is numerically investigated. The inner surface of the tubes is subjected to constant heat flux. In the GMF region, the Brinkman extended Darcy flow model and the local thermal non-equilibrium (LTNE) model are used to predict fluid and thermal transport. At the layer-layer interface in GMF, fluid temperature and solid energy are assumed to be continuous. At the GMF-fluid interface, no-slip coupling conditions are used to couple flow and heat transfer of the foam and free regions. Velocity distribution, temperature profile, the friction factor and Nusselt number in partially-filled GMF tubes are calculated. The results show that the heat transfer performance and flow resistance of GMFs are heavily dependent on porosity, pore density and GMF thickness gradients.